Anarkhisme sebagai Gejala Sosial - Agung Aditya; Zulfa Amalia Rachim; Purwanto; Irawaty; Suhadi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The situation of anarchism in Indonesia is a result of a conflict between state law and living law and is due to social, economic, and political inequality. This study seeks to understand anarchism, not only as a criminal act, but as a socio-legal condition consisting of a structural complaint and a crisis of legal legitimacy. To understand how state law, living law, and social order interconnect to cause the oppressed to act anarchistically, the study uses empirical legal research along with a socio-legal approach and legal literature research. The results of the study show social inequality coupled with arbitrary law enforcement results in a loss of legal legitimacy which arguably weakens the law and transforms it into a tool of oppression rather than a tool of justice. Thus, people’s resistance to structural injustices is expressed in the form of legal defiance. An enhanced model of legal responsiveness is warranted which consists of participative regulatory adjustments, the integration of restorative justice, the broadening of justice system gates, oversight of economic policy, and the digital revolution. The system change, to comply with the demands of justice and social order, places the consolidation of a responsive legal system, and not a repressive one, as a necessity of legal and socio-political order.